p53 binds human telomeric G-quadruplex in vitro - Adámik, Matej; Kejnovská, Iva; Bažantová, Pavla; Petr, Marek; Renčiuk, Daniel; Vorlíčková, Michaela; Brázdová, Marie (Biochimie, 2016)
The tumor suppressor protein p53 is a key factor in genome stability and one of the most studied of DNA binding proteins. This is the first study on the interaction of wild-type p53 with guanine quadruplexes formed by the human telomere sequence. Using electromobility shift assay and ELISA, we show that p53 binding to telomeric G-quadruplexes increases with the number of telomeric repeats. Further, p53 strongly favors G-quadruplexes folded in potassium over those formed in sodium, thus indicating the telomeric G-quadruplex conformational selectivity of p53. The presence of the quadruplex-stabilizing ligand, N-methyl mesoporphyrin IX (NMM), increases p53 recognition of G-quadruplexes in potassium. Using deletion mutants and selective p53 core domain oxidation, both p53 DNA binding domains are shown to be crucial for telomeric G-quadruplex recognition.
Keywords: mutace; tandemové repetitivní sekvence; Tumor Suppressor Protein p53; Enzyme-Linked Immunosorbent Assay; draslík; Base Sequence; Oligonucleotides; oligonukleotidy; vazebná místa; Potassium; retardační test; vazba proteinů; telomery; Binding, Competitive; DNA; lidé; Telomere; Mutation; Protein Binding; Tandem Repeat Sequences; G-kvadruplexy; mesoporfyriny; G-Quadruplexes; ELISA; Circular Dichroism; kompetitivní vazba; DNA-protein interaction; nádorový supresorový protein p53; Mesoporphyrins; sekvence nukleotidů; G-quadruplex; Telomere DNA; p53 protein; Electrophoretic Mobility Shift Assay; cirkulární dichroismus; Binding Sites; Humans